Isolation, biochemical characterization and crystallization of the p15gag proteinase of myeloblastosis associated virus expressed in E. coli - Pichová, I; Strop, P; Sedlácek, J; Kaprálek, F; Benes, V; Trávnícek, M; Pavlícková, L; Soucek, M; Kostka, V; Foundling, S (The International journal of biochemistry, 1992)
1. The p15gag proteinase responsible for the processing of the polyprotein precursor of the myeloblastosis associated virus was obtained by a recombinant technique in an E. coli expression system. The massive expression of the intentionally truncated precursor (Pr25lac-delta gag) was accompanied by its structurally correct processing. 2. Three procedures for the purification of the recombinant proteinase from both the cytoplasmic fraction and the inclusion bodies were developed. 3. The purified proteinase was compared with the authentic proteinase isolated from MAV virions by N-terminal sequence analysis and amino acid analysis, molecular weight determination, reverse-phase HPLC and FPLC elution profiles, electrophoretic mobility and isoelectric point determination, and activity assays with proteins and synthetic substrates. The identity of both enzymes was shown. 3. Contrary to reported data, the amino acid sequence of the p15gag proteinase differs from the sequence of the homologous Rous sarcoma virus proteinase in one residue only, as follows from cDNA sequencing. 4. Crystallization of the proteinase from a citrate-phosphate buffer at pH 5.6 afforded hexagonal crystals which diffracted well as 2.3 A without deterioration.
Keywords: Molecular Sequence Data; Avian Myeloblastosis Virus; elektroforéza v polyakrylamidovém gelu; sekvence aminokyselin; krystalizace; izoelektrický bod; Isoelectric Point; rekombinantní proteiny; aspartátové endopeptidasy; DNA virů; posttranslační úpravy proteinů; Chromatography, High Pressure Liquid; Aspartic Acid Endopeptidases; vysokoúčinná kapalinová chromatografie; Base Sequence; sekvence nukleotidů; Gene Products, gag; Electrophoresis, Polyacrylamide Gel; virus ptačí myeloblastózy; cytoplazma; Escherichia coli; Protein Processing, Post-Translational; Crystallization; Amino Acid Sequence; DNA, Viral; genové produkty gag; Cytoplasm; molekulární sekvence - údaje; Recombinant Proteins